Production and Characterization of Polypropylenecarbon Nanotube Nanocomposites - Abd Razak, Jeefferie (2009)
At the first stage in this research, the multi-walled carbon nanotubes (MWCNTs) were grown by using the floating catalysts chemical vapor deposition (FC-CVD) method. The produced MWCNTs were characterized by using the scanning electron microscopy (SEM), transmission electron microscopy (TEM) and the high resolution transmission electron microscopy (HRTEM). The MWCNTs was incorporated into polypropylene (PP) to produce the PP/MWCNTs nanocomposites through the direct melt compounding process using an internal mixer. The mixer parameters were varied to determine the best parameter to produce the nanocomposites. It was determined through the tensile test which performed on every nanocomposite which fabricated from the various combinations of parameters. The best parameters to produce the nanocomposites were at the temperature of 175°C, rotor speed of 60 rpm and the compounding time of 8 minutes. In the next stage, the effect of filler loading was studied. The filler loading was varied from 0, 0.25, 0.50, 0.75 and 1.00wt.%. The best tensile properties was observed in the nanocomposites with 0.75wt.% of MWCNTs, with the improvement of 42.82% and 126.90% of the tensile strength and tensile modulus, compared to the virgin PP matrix. The validation of the tensile test data was carried out by using the historical data design from the Response Surface Methodology (RSM) with the aid of the Design Expert Software 6.10. The PP/MWCNTs nanocomposites which compounded from the best processing parameter were further characterized for other properties. Physical test on the nanocomposites density was revealed that the density is decreased with the increasing percentage of MWCNTs addition. This condition gives benefit on the weight saving of the materials. Fourier Transform Infra Red (FTIR) and X-Ray diffraction analysis disclosed that the melt blending between the PP matrix and MWCNTs filler is entirely physical-mechanical blending, without involving any chemical interaction. This further explained the reinforcement behavior of the MWCNTs within the PP matrix. Furthermore, TEM images of the nanocomposites surface confirmed an excellent dispersion and distribution of the MWCNTs in the PP matrix. This condition was supported by the significant improvement of the flexural strength, flexural modulus, impact strength, and storage modulus and loss modulus properties of the fabricated nanocomposites. In overall, the proper selection of the melt blending processing parameter and the use of low filler loading was significantly helped to disperse and distribute the MWCNTs homogenously within the PP matrix, resulting major improvements to the many of the properties studied